2014
DOI: 10.1002/2013gb004574
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of aeolian sand and dust to iron fertilization of phytoplankton blooms in southwestern Ross Sea, Antarctica

Abstract: Iron is a limiting micronutrient for primary production in the Ross Sea, Antarctica. Recent observations reveal low dissolved Fe (dFe) concentrations in the Ross Sea polynya following high initial rates of primary production in summer, after the dFe winter reserve has been consumed. Significant new sources of dFe are therefore required to further sustain phytoplankton blooms. Iron from aeolian sand and dust (ASD) released from melting sea ice is one potential source. To constrain aeolian Fe inputs, we determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 104 publications
(190 reference statements)
2
82
1
Order By: Relevance
“…[], MEDUSA‐RS also does not include aeolian deposition. A sensitivity analysis revealed that realistic concentrations of atmospheric iron deposition in the Ross Sea negligibly affect the modeled phytoplankton, in accordance with field‐based estimates [ Winton et al ., ]. All model equations are provided in the supporting information Tables S1 and S2.…”
Section: Methodsmentioning
confidence: 99%
“…[], MEDUSA‐RS also does not include aeolian deposition. A sensitivity analysis revealed that realistic concentrations of atmospheric iron deposition in the Ross Sea negligibly affect the modeled phytoplankton, in accordance with field‐based estimates [ Winton et al ., ]. All model equations are provided in the supporting information Tables S1 and S2.…”
Section: Methodsmentioning
confidence: 99%
“…The evidence supporting very small atmospheric dust Fe inputs has been well discussed elsewhere; atmospheric deposition is very likely to be insignificant relative to other fluxes to the euphotic zone (Sedwick et al 2011;Gerringa et al, 2012;Gao et al, 2013;Planquette et al, 2013), although aerosol concentrations have yet to be quantified in the ASP region. In other Antarctic regions with substantial exposed unconsolidated sediments on the proximal continent, dust sources may be somewhat more important (Winton et al, 2014).…”
mentioning
confidence: 99%
“…, with locally higher deposition confined to the McMurdo Sound area [Winton et al, 2014]. Postconvective vertical mixing by turbulent diffusion and/or episodic upwelling by mesoscale and submesoscale fronts and eddies may supply additional dFe during the growing season.…”
mentioning
confidence: 99%